Theoretical and experimental study on the reaction route for the FVP of 2-thioxohexahydroquinazolinones - Peláez, Walter José (2012)
Structural and conformational analyses through the use of different spectrometric techniques as well as DFT calculations performed to analyze the results of FVP reactions on pure cis as well as pure trans 2-thioxo-hexahydroquinazolinones yielding isothiocyanates as main products have been carried out. With these, we could assess the specific tautomer/isomer/conformer that produces the products in each FVPreaction. It was confirmed that for both isomers, the reaction takes place from the thiol tautomer, and for the special case of the cis isomer, the conformer involved is the N(1)-in.